Connecting leadership with learning : a framework for reflection, planning, and action - Copland, Michael A. (Association for Supervision and Curriculum Development, 2006)
What kind of leadership makes learning possible for all students? How can school leaders help teachers increase their knowledge and improve their instructional abilities? What actions should leaders take to ensure that learning occurs? In Connecting Leadership with Learning: A Framework for Reflection, Planning, and Action, Michael A.